Use of videotutorials with H5P questions in lab lessons: An experience in Science and Engineering studies - Cerdà Pino, Joan; Amengual Pou, Arnau; Torrens Serra, Joan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The use of interactive videotutorials (VTI) in lab lessons in science and engineering degrees as complementary resources to the traditional written manuals have been analysed by means of satisfaction surveys taken by the students. Results show a positive impact on the self-learning of students as well as an improvement on their lab skills. However, the inclusion of assessment questions in the videos has been described as negative because of the increase in the workload.